Q: What is 6x plus 3y plus 6y-2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

no

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

4x-2y

3x + 6y + 6x = 9x + 6y which can be factorised as 3(3x +2y)

Related questions

-x+3y+6x-6y=5x-3y

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

It is the same as: 6x+4y

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

6x+3y = 8 3y = -6x+8 y = -3x+8/3 The slope of the line is -3

no

y=(6x-5)/3

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

6x+3y = 18 3y = -6x+18 y = -2x+6 Therefore the slope is -2 and the y intercept is 6

The slope-intercept form of the equation of a line is y = mx + b, wher m = slope and b = y-intercept.2 - 3y + 6x = 0 just solve for y2 - 2 - 3y + 6x - 6x = 0 - 6x - 2-3y = - 6x - 2-3y/-3 = - 6x/-3 - 2/-3y = 2x + 2/3

6x - y

4x-2y